2019
DOI: 10.1111/geb.12908
|View full text |Cite
|
Sign up to set email alerts
|

Local temperature and ecological similarity drive distributional dynamics of tropical mammals worldwide

Abstract: Aim Identifying the underlying drivers of species’ distributional dynamics is critical for predicting change and managing biological diversity. While anthropogenic factors such as climate change can affect species distributions through time, other naturally occurring ecological processes can also have an influence. Theory predicts that interactions between species can influence distributional dynamics, yet empirical evidence remains sparse. A powerful approach is to monitor and model local colonization and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 79 publications
(112 reference statements)
0
12
0
Order By: Relevance
“…Recently, the growing interest in biotic interactions has led to a myriad of different statistical methods to study whether species are found together less often (negative association in occupancy; segregation) or more often (positive association in occupancy; aggregation) than predicted by random chance only (see Dormann et al, 2018 for an overview). These techniques include single species distribution and dynamic occupancy models in which other species' occupancy (Heikkinen et al, 2007), phylogenetic relationships (Morales-Castilla et al, 2017) and/or ecological similarity (Beaudrot et al, 2019) are included as covariates. Other examples include partial correlation networks (García-Girón et al, 2020), and different ordination methods, such as distance-based redundancy analysis (Bottin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the growing interest in biotic interactions has led to a myriad of different statistical methods to study whether species are found together less often (negative association in occupancy; segregation) or more often (positive association in occupancy; aggregation) than predicted by random chance only (see Dormann et al, 2018 for an overview). These techniques include single species distribution and dynamic occupancy models in which other species' occupancy (Heikkinen et al, 2007), phylogenetic relationships (Morales-Castilla et al, 2017) and/or ecological similarity (Beaudrot et al, 2019) are included as covariates. Other examples include partial correlation networks (García-Girón et al, 2020), and different ordination methods, such as distance-based redundancy analysis (Bottin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…If ecologically and functionally similar species with similar habitat preferences are negatively associated, this can be interpreted as a result of interspecific competition (Kohli et al, 2018;Mönkkönen et al, 2017). Indeed, the notion that ecologically similar species should compete more intensively than ecologically dissimilar species is not new (Darwin, 1859), and ecological similarity has been used as a proxy for the probability that species compete with one another (Beaudrot et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Latitudinal or longitudinal gradients of climatic factors can also influence the distribution and persistence of some species at a regional scale (e.g. due to physiological restrictions in extreme temperatures; Beaudrot et al, 2019). However, these processes are not mutually exclusive leading to a whole range of responses to land-use changes that affect community similarity (Dormann et al, 2007;Newbold et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Over 50% of the park's border is classified as fragmented landscape (Ahumada et al., 2011). Nevertheless, little forest cover change has been observed within the protected area in recent years (Beaudrot et al., 2019), which suggests that human disturbance from illegal logging has been minimal.…”
Section: Methodsmentioning
confidence: 99%